UNDERSTANDING FOOD SECURITY THROUGH THE LENS OF ISLAMIC FRAMEWORK: A RESEARCH TREND REVIEW - Ismail, Ahmad Syihan; Hamid, Siti Nur Hazirah; Abdullah, Yusuf Marlon (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
Food security has become an increasingly urgent global issue, particularly when viewed through the multifaceted lens of policy and ethical frameworks such as Islam. Despite the vast body of literature addressing food-related challenges, there remains a significant gap in understanding how Islamic principles intersect with food security discourse. This study aims to explore the research trends and scholarly contributions to the field of food security from an Islamic framework perspective. Using a bibliometric approach, we employed Scopus as the primary database and applied an advanced search strategy incorporating the keywords “food,” “security,” and “policy.” The inclusion criteria were limited to peer-reviewed journal articles in English, published between 2009 and 2025. Data cleaning and refinement were conducted using OpenRefine, while trend visualization, co-authorship networks, and keyword co-occurrence analyses were carried out using Scopus Analyzer and VOSviewer software. A total of 886 relevant publications were retrieved and analyzed. The findings indicate a growing scholarly interest in food security topics, with prominent contributions from countries such as the United States, United Kingdom, and Australia. Key themes identified include agricultural policy, sustainability, climate change, and nutrition, while co-authorship analysis revealed strong international collaborations in this field. Despite the dominance of Western-centric perspectives, there is an emerging body of literature that aligns food security discourse with Islamic values such as justice, equity, and stewardship. This bibliometric review not only maps the existing knowledge landscape but also highlights the potential for integrating Islamic ethical constructs into food security policy discussions. The study concludes by emphasizing the need for more interdisciplinary and faith-based approaches in future research to address both global challenges and cultural contextual solutions.